2015
DOI: 10.1016/j.anbehav.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Quiet threats: soft song as an aggressive signal in birds

Abstract: Theory suggests that aggressive signals must be costly if they are to be reliable. Recent research in birds has shown, however, that in many species the best predictors of impending attack are low amplitude vocal signals, soft songs or soft calls, that seem cheap to produce and easy to cheat. This observation leads to two related but separate questions: 1) Why use low amplitude signals to communicate aggressiveness? and 2) What maintains the reliability of soft signals of aggression? We review potential answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 72 publications
1
44
2
Order By: Relevance
“…Soft songs were of unusually low amplitude and fairly easy to identify in the field after spending time observing red-eyed vireos throughout the 2014e2015 field seasons. Soft songs have received recent attention because they may be associated with aggressive intent in several songbird species (Akçay, Anderson, Nowicki, Beecher, & Searcy, 2015). There are no previous reports of soft song in red-eyed vireos; however, our preliminary observations suggested that they occur in this species, just as they appear to be common among many other songbirds (Dabelsteen, McGregor, Lampe, Langmore, & Holland, 1998;Reichard & Welklin, 2015).…”
Section: Playback Experimentsmentioning
confidence: 52%
See 1 more Smart Citation
“…Soft songs were of unusually low amplitude and fairly easy to identify in the field after spending time observing red-eyed vireos throughout the 2014e2015 field seasons. Soft songs have received recent attention because they may be associated with aggressive intent in several songbird species (Akçay, Anderson, Nowicki, Beecher, & Searcy, 2015). There are no previous reports of soft song in red-eyed vireos; however, our preliminary observations suggested that they occur in this species, just as they appear to be common among many other songbirds (Dabelsteen, McGregor, Lampe, Langmore, & Holland, 1998;Reichard & Welklin, 2015).…”
Section: Playback Experimentsmentioning
confidence: 52%
“…Soft songs have received substantial attention recently, but little is known about why birds use them to indicate aggressive intent and how these signals remain reliable (Akçay et al, 2015). Despite this, a wide array of animals, including birds (Akçay et al, 2015) and some mammals (Gustison & Townsend, 2015), are known to use soft vocalizations in aggressive contexts, and red-eyed vireos now join these animals. Two measures of red-eyed vireos' playback responses showed no differences in response to neighbours versus strangers.…”
Section: Neighbourestranger Discriminationmentioning
confidence: 99%
“…The low amplitude of these signals appears to be easy to explain, and the reasons for limiting the active space of the signal are rather obvious. On the other hand, some bird species produce soft songs or calls during aggressive interactions as a means of territorial defence (e.g., Akçay, Anderson, Nowicki, & Beecher, ; Ręk & Osiejuk, ; Searcy & Nowicki, ; Xia, Liu, Alström, Wu, & Zhang, ). The link between signal function and low amplitude in this context is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is currently an open debate over why low‐amplitude rather than high‐amplitude signals are the most aggressive signal in many songbird species, especially as the latter seems more intimidating (Akçay et al. ; Reichard & Anderson ). Early work suggested males’ benefit from using low‐amplitude signals that limit eavesdropping by predators and other conspecifics (Dabelsteen et al.…”
Section: Discussionmentioning
confidence: 99%